Evaluation of self-boring pressuremeter tests in Boston blue clay / by Charles C. Ladd, John T. Germaine, Mohsen M. Baligh, Suzanne M. Lacasse. - Ladd, Charles C. (Charles Cushing); Germaine, John T.; Baligh, Mohsen M.; Lacasse, Suzanne M.; United States. Federal Highway Administration. (Tufts University. Tisch Library., 2019)
1 online resource (438 pages) : illustrations.; This report is made available as part of the Dr. Charles C. Ladd Collection. For more information, contact Dr. Lewis Edgers (ledgers@tufts.edu) or Dr. Jack Germaine (john.germaine@tufts.edu) in the Tufts University Civil and Environmental Engineering department.